The Uzbek Model of Development of the National Idea and Its Peculiarities - Nargiza, Nabieva (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes various concepts of the Uzbek model of development of the national idea and its specific features. sociological research and data were re-examined. The national idea is inseparable from the feeling of homeland. That is why the most important feature of the national idea is to deeply understand that the fate of every Uzbek, that is, each of us, depends on the development of this state and society, to turn this feeling into a practical action, a way of life.